Importance of Fc Receptor γ-Chain ITAM Tyrosines in Neutrophil Activation and in vivo Autoimmune Arthritis - Németh, Tamás; Futosi, Krisztina; Szabó, Marcell; Aradi, Petra; Saito, Takashi; Mócsai, Attila; Jakus, Zoltán (Frontiers in Immunology, 2019)
Activating Fcγ receptors associated with Fc receptor γ-chain (FcRγ) are critical for mediating neutrophil effector functions in immune complex-mediated autoimmune diseases. FcRγ contains ITAM tyrosines and the in vivo role of these tyrosines has not been defined in neutrophils and arthritis. In this study, the in vivo functions of FcRγ ITAM tyrosines were characterized using wild type and ITAM tyrosine mutant (Y65F/Y76F) transgenic mice crossed to an FcRγ-deficient genetic background. FcRγ-deficient neutrophils showed undetectable cell surface expression of the activating Fcγ receptor IV, defective immune complex-induced superoxide production, degranulation and spreading. Although the re-expression of both the wild type and the ITAM tyrosine mutant (Y65F/Y76F) FcRγ could restore activating Fcγ receptor expression of FcRγ-deficient neutrophils, only the wild type transgenic form could mediate Fcγ receptor-dependent effector functions. In contrast, neutrophils carrying ITAM tyrosine mutant FcRγ were unable to produce superoxide, mediate degranulation and perform active spreading. In addition, our results confirmed the protection of FcRγ-deficient mice from autoimmune arthritis. Importantly, the presence of the wild type FcRγ transgene, in contrast to the ITAM tyrosine mutant transgene, partially reversed autoimmune arthritis development. The reversing effect of the wild type transgene was even more robust when animals carried the wild type transgene in a homozygous form. Collectively, FcRγ ITAM tyrosines play a critical role in the induction of neutrophil effector responses, the initiation and progression of an autoantibody-induced experimental arthritis in vivo, indicating a signaling, rather than just a receptor stabilizing function of the molecule.